A Lightweight Buyer-Seller Watermarking Protocol. (12th August 2008) - Wu, Yongdong; Pang, Hweehua
Abstract : The buyer-seller watermarking protocol enables a seller to successfully identify a traitor from a pirated copy, while preventing the seller from framing an innocent buyer. Based on finite field theory and the homomorphic property of public key cryptosystems such as RSA, several buyer-seller watermarking protocols (N. Memon and P. W. Wong (2001) and C.-L. Lei et al. (2004)) have been proposed previously. However, those protocols require not only large computational power but also substantial network bandwidth. In this paper, we introduce a new buyer-seller protocol that overcomes those weaknesses by managing the watermarks. Compared with the earlier protocols, ours isn times faster in terms of computation, wheren is the number of watermark elements, while incurring onlyO ( 1 / l N ) times communication overhead given the finite field parameterl N . In addition, the quality of the watermarked image generated with our method is better, using the same watermark strength.